Dieta de Odocoileus virginianus (Artiodactyla: Cervidae) en un bosque templado del norte de Oaxaca, México. - González, Graciela (2012)
The Sierra Madre de Oaxaca region, located in the Northern state of Oaxaca, Mexico, is an area of forest ecosystems subject to high exploitation rates, although in some areas its temperate forests are conserved by indigenous community initiatives that live there. We analyzed the diet of white tailed-deer (Odocoileus virginianus) in the localities of Santa Catarina Lachatao and San Miguel Amatlán from June 1998 to August 1999. Sampling was done during both the wet and dry seasons, and included the observation of browsing traces (238 observations), microhistological analysis of deer feces (28 deer pellet-groups), and two stomach content analysis. The annual diet of white-tailed deer was composed of 42 species from 23 botanical families. The most represented families in the diet of this deer were Fagaceae, Asteraceae, Ericaceae and Fabaceae. There were significant differences in the alpha diversity of the diet during the wet and dry seasons (H?=2.957 and H?=1.832, respectively). The similarity percentage between seasons was 56%. Differences in plant species frequency were significantly higher during the wet season. Herbaceous plants made up the greatest percentage of all the species consumed. The preferred species throughout the year were Senecio sp. (shrub), Sedum dendroideum (herbaceous), Arctostaphylos pungens (shrub) and Satureja macrostema (shrub). Diet species richness was found to be lower than that observed in a tropical forest (Venezuela), tropical dry forest (Mexico) and temperate deciduous and mixed forest (Mexico), but similar to the diet species richness observed in a tropical dry forest (Costa Rica) and temperate coniferous and deciduous forests (USA)